ADAD2 functions in spermiogenesis and piRNA biogenesis in mice. (14th February 2023) - Lu, Yonggang; Nagamori, Ippei; Kobayashi, Hisato; Kojima‐Kita, Kanako; Shirane, Kenjiro; Chang, Hsin‐Yi; Nishimura, Toru; Koyano, Takayuki; Yu, Zhifeng; Castañeda, Julio M.; Matsuyama, Makoto; Kuramochi‐Miyagawa, Satomi; et al.
Abstract: Background: Adenosine deaminase domain containing 2 (ADAD2) is a testis‐specific protein composed of a double‐stranded RNA binding domain and a non‐catalytic adenosine deaminase domain. A recent study showed that ADAD2 is indispensable for the male reproduction in mice. However, the detailed functions of ADAD2 remain elusive. Objectives: This study aimed to investigate the cause of male sterility in Adad2 mutant mice and to understand the molecular functions of ADAD2. Materials and methods: Adad2 homozygous mutant mouse lines, Adad2 –/– and Adad2 Δ/Δ, were generated by CRISPR/Cas9. Western blotting and immunohistochemistry were used to reveal the expression and subcellular localization of ADAD2. Co‐immunoprecipitation tandem mass spectrometry was employed to determine the ADAD2‐interacting proteins in mouse testes. RNA‐sequencing analyses were carried out to analyze the transcriptome and PIWI‐interacting RNA (piRNA) populations in wildtype and Adad2 mutant testes. Results: Adad2 –/– and Adad2 Δ/Δ mice exhibit male‐specific sterility because of abnormal spermiogenesis. ADAD2 interacts with multiple RNA‐binding proteins involved in piRNA biogenesis, including MILI, MIWI, RNF17, and YTHDC2. ADAD2 co‐localizes and forms novel granules with RNF17 in spermatocytes. Ablation of ADAD2 impairs the formation of RNF17 granules, decreases the number of cluster‐derived pachytene piRNAs, and increases expression of ping‐pong‐derived piRNAs. Discussion and conclusion: In collaboration with RNF17 and other RNA‐binding proteins in spermatocytes, ADAD2 directly or indirectly functions in piRNA biogenesis.